Pedagogical Conditions of Young Learners’ Social Competence Formation in the Educational Process of Modern Ukrainian Primary School - Pits, Iryna; Byhar, Hanna; Shevchuk, Krystyna; Makoviichuk, Olesia (Pedagogical Discourse, 2020)
Up to date, there are growing appeals for the Ukrainians’ social security and protection under the conditions of increasing technogenic and growing informational load, leading to the risk of destroying personality. Previous studies have emphasized that social competence becomes more complicated as children grow older, and most intervention efforts for this age group target individual skills, the family, and the classroom setting. It is of critical value to nurture physically robust and socially developed full-fledged citizens, since there is a lack of the national rigorous study in the relevant domain. The aim of the research is to further extend and design social interaction research, the theoretical discourse and practical vision of fostering and improving primary schoolchildren’s social competence in the new Ukrainian school setting. Taking a broad view on different approaches to the concept of social competence, we consider it a person’s integrative capacity, formed in the process of his/her socialization experience. Thus, sharing societal norms and expectations, motives, values, emotional and practical skills, and knowledge, a person gains effectiveness of interaction with other people, independently finds constructive solutions to problems in real life situations, and rapidly adapts to new living conditions. Fostering and improving social competence in primary schoolchildren in the New Ukrainian School setting should become an indispensable part of school-parents’ partnership in designing a variety of strategies and practices for improving schoolchildren’s social knowledge and skills, and respectively making young learners balancing studies and social life.